Dinamika Pengelolaan Sampah Rumah Tangga di Desa Gunung Sari Kecamatan Citeureup, Kabupaten Bogor - Francisca Gita Anjani; Pudji Muljono (Department of Communication and Community Development Sciences and PAPPI (Perhimpunan Ahli Penyuluhan Pembangunan Indonesia), 2015)
Domestic Wasted management program is one of PT Indocement's CSR conducted in Gunung Sari Village. This research aimson the evaluation of wasted management program that has been running since 2009. The evaluation was conducted using CIPPconcept from Stufflebeam by analyzing content, input, process, and final product as an outcome from this program. This researchillustrated both the supporting and inhibiting factors from the domestic wasted management program and also described theproceeding programs for these past 5 years. The population for this research was represented by 120 domestic house wivesas corespondent, addressed in RW 04. Domestic wasted management program in Gunung Sari Village is running well. Thesupporting factors for this program are the subsidy cost from PT. Indocement CSR funds, the awareness of UPK managementto be independent, creativity and the society's awareness for a cleaner environment. Meanwhile the inhibiting factors are themarketing for the final product and the lack of communications between the stakeholders.Keywords: evaluation, CIPP, CSR, domestic wasted management